N′-Cyclododecylidenepyridine-4-carbohydrazide - Lemmerer, Andreas (International Union of Crystallography, 2012)
The title compound, C(18)H(27)N(3)O, is a derivative of the antituberculosis drug isoniazid (systematic name: pyridine-4-carbohydrazidei). The crystal structure consists of repeating C(4) chains along the b axis, formed by N—H⋯O hydrogen bonds with adjacent amide functional groups that are related by a b-glide plane. The cyclododecyl ring has the same approximately ‘square’ conformation, as seen in the parent hydrocarbon cyclododecane.